For those “disenchanted” who leave. Some intuitions for pastoral care - González Pacheco, Luis Donaldo (Razón y fe, 2020)
This article aims to point out very basic guidelines so as not to forget that those who leave the Church go out because they do not feel welcome or get lost because they do not know what they believe. We will refer to them as disenchanted. Remembering that they are men and women who, called to Transcendence, walk paths to God, who assimilate things in a personal and never uniform way, and who, in the end, are included in the “go and make disciples of all nations” (Mt 28:19), the main task of the Church and of her pastoral agents.